Pengaruh Viral Marketing terhadap Brand Equity pada Pengguna Smartphone Samsung di Yogyakarta - Ratnaningsih, Endang (Akmenika, 2016)
This research conducted to analyze the impact of viral marketing to brand equity of Samsung smartphone. The Samsung smartphone was dominating the Indonesian smartphone's market in 2015, since the online marketing and the viral marketing became the buzz word for business in the last ten years. This study focused to anempirical study that was conducted to 100 undergraduate students in Yogyakarta.The data were collected from consumers of Samsung smartphone and was tested forits construct validity and reliability and regression was applied to test the hypotheses. This findings indicated that viral marketing had a significant and positive influence to brand equity of Samsung smartphone, and showed that viral marketing had a huge potential distribution channel to marketing the product.